Implementasi Fuzzy Logic Dalam Monitoring Infus Berbasis Internet of Things (IoT) - Maulana, Moch Sigit Rizky; Rohana, Tatang; Mudzakir, Tohirin Al (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The main function of the infusion is to provide fluids to the patient, the availability of the patient's infusion fluids must always be considered periodically. The increasing number of patients and the limited number of medical personnel is causing uncontrollable delays in changing IV fluids. Blockage in the infusion line can cause air embolism in the blood vessels, which can result in death. By using an automatic infusion monitoring system, the risk of delays in replacing patient infusion fluids can be reduced. To calculate the ambiguity of sensor values, the fuzzy mamdani method was used in this study. Load Cell, HX711 and IR HC-89 are the sensors used. The value generated by the sensor is in the form of NodeMCU ESP32 input which is used by the mamdani method to determine the value in the form of output. The command to turn on the buzzer is the value of the output. Maximizing the effectiveness of the infusion monitoring system is designed with the Mamdani calculation method. The difference in value with an average weight of 5.9% infusion and 5.54 Vo drops is obtained from the results of a comparison of sensor testing with manual tools. Infusion monitoring obtains an accuracy rate of 92% from the test results on system performance.